2016
DOI: 10.1002/2016jf003871
|View full text |Cite
|
Sign up to set email alerts
|

Effects of basin bottom slope on jet hydrodynamics and river mouth bar formation

Abstract: River mouth bars are strategic morphological units primarily responsible for the development of entire deltaic systems. This paper addresses the role of receiving basin slope in the hydrodynamics of an exiting sediment‐laden turbulent jet and in resulting mouth bar morphodynamics. We use Delft3D, a coupled hydrodynamic and morphodynamic numerical model, along with a theoretical formulation to reproduce the physics of the problem, characterized by a fluvially dominated inlet free of waves and tides. We propose … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 78 publications
(229 reference statements)
0
12
0
Order By: Relevance
“…However, scaling of shallow water jets by Özsoy and Ünlüata (1982) showed that in the presence of significant basinward slopes, jets can converge or contract when the basinward bed slope ( −∇ ⋅ ⃗ ⃗ ≈ ∇ℎ ⋅ ⃗ ⃗ > 0) exceeds the dimensionless friction factor (Cf). Recent numerical modelling by Jiménez-Robles et al (2016) also shows that jets can exhibit 10 flow direction convergence when basinward slopes exceed ~1%. The bathymetric complexity and significant unchannelized flows on the Wax Lake Delta prevent us from rigorously applying the findings of either study to the delta front of the Wax Lake Delta, but note that there is a physical basis for flow direction convergence on delta fronts that supports the convergence we observe in streaklines.…”
Section: Bathymetry and Flow Patterns On River-dominated Deltasmentioning
confidence: 96%
“…However, scaling of shallow water jets by Özsoy and Ünlüata (1982) showed that in the presence of significant basinward slopes, jets can converge or contract when the basinward bed slope ( −∇ ⋅ ⃗ ⃗ ≈ ∇ℎ ⋅ ⃗ ⃗ > 0) exceeds the dimensionless friction factor (Cf). Recent numerical modelling by Jiménez-Robles et al (2016) also shows that jets can exhibit 10 flow direction convergence when basinward slopes exceed ~1%. The bathymetric complexity and significant unchannelized flows on the Wax Lake Delta prevent us from rigorously applying the findings of either study to the delta front of the Wax Lake Delta, but note that there is a physical basis for flow direction convergence on delta fronts that supports the convergence we observe in streaklines.…”
Section: Bathymetry and Flow Patterns On River-dominated Deltasmentioning
confidence: 96%
“…Hydrodynamically, a mouth bar develops when sedimentladen jets exit a channel mouth into a body of standing water. Some studies have also focused on the influence of various external parameters on these mouth bars such as discharge, waves, tides and basin slope (Leonardi et al, 2013;Jimenez-Robles et al, 2016;Gao et al, 2019). Wright (1977) was one of the first to describe mouth bar deposition in terms of inertial, frictional and buoyant forces, in addition to reworking forces (tides, waves).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the detailed morphodynamic mechanisms of the formation of individual mouth bars have been investigated using numerical simulations in Delft3D (Edmonds and Slingerland, 2007;Geleynse et al, 2010;Esposito et al, 2013;Mariotti et al, 2013;Canestrelli et al, 2014). Some studies have also focused on the influence of various external parameters on these mouth bars such as discharge, waves, tides and basin slope (Leonardi et al, 2013;Jimenez-Robles et al, 2016;Gao et al, 2019). This paper investigates how the upstream sediment supply composition is translated not only to the mouth bars, but across the whole range of architectural elements.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, works focused on offshore plume processes are carried out in a framework of no connectivity with the issuing channel. Related fluid dynamics and sediment patterns on the oceanic region are based on a boundary condition at the channel mouth (Wright, 1977;Özsoy, 1986;Wang, 1984;Leonardi et al, 2013Leonardi et al, , 2014Fagherazzi et al, 2015;Jiménez-Robles et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…These equations are dinamically coupled to the flow and sediment patterns in the offshore region by means of a sufficiently simple analytical model of plume hydrodynamics that reduces drastically the computational effort. In the near field, during the ebb-phase tidal plumes behave as a bounded, sediment-laden, turbulent jet (Rajaratnam, 1976;Joshi, 1982;Ortega-Sánchez et al, 2003;Jiménez-Robles et al, 2016). The approximate equations for the jet flow and sediment patterns were derived by Özsoy and Ünlüata (1982) and Özsoy (1986) respectively.…”
Section: Introductionmentioning
confidence: 99%